Pengaruh Interval Training dan Shuttle Run Terhadap Daya Tahan Cardio Vascular pada Ekstrakulikuler Futsal - Puriana, Ramadhany Hananto; Putranto, Nico Yudho; Aran, Kristoforus Ado; Azmi, Khairul; Dinata, Karno; Kusuma, Angga Indra (Jurnal Porkes, 2024)
This study aims to examine the bleep test on cardiovascular endurance at SMK Negri 2 Surabaya. This research uses quantitative research with experimental methods. In this study used a two-group design with pretest and posttest. The sample in this study were 10 students of SMK Negri 2 Surabaya. The results of experimental research 1 sig value. (2 tailed) of 0.000 < 0.05 then Ha is accepted which means there is an effect of Interval training on cardiovascular endurance, experiment 2 obtained a sig value. (2 tailed) of 0.004 <0.05, then Ha is accepted, it can be concluded that there is an average difference in pretest results. The above results mean that interval training and shuttle run training is one of the most effective exercises to improve physical condition.  This is due to the provision of interval training and shuttle run exercises. After getting data and calculating it can be said that interval training and shuttle run can increase the cardiovascular endurance of futsal extracurricular SMKN 2 Surabaya.